Can seedlings' physiological information improve vegetation distribution predictions at local scales? - Calleja Apéstegui, Felipe (2020)
Physiological information has been suc- cessfully included in marine Species Distribution Models (SDM) before, but few have considered a previous development stage that could have affected the present-day distribution of the species at local scales. The aim of this study is to analyze the inclusion of physiological information of seedling survival on a correlative SDM based on adult present-day pres- ences. The species were the invasive shrub Baccharis halimifolia and the native saltmarsh Juncus maritimus. For each species, five SDM were established using different approaches: using only experimentally derived physiological data, a correlative model with environmental predictors, additive combinations of presence/absence maps derived from the previous models, and a correlative model with the physiological data as a predictor variable. For B. halimifolia, the inclusion of the physiological data as a predictor variable yielded better results than with the other approaches; with J maritimus, this inclusion achieved an accuracy as high as the model with only environ- mental variables as predictors. The additive combina- tions generated less accurate models but offered possible advantages in future specialized studies. The results for B. halimifolia could extrapolate to other invasive species that rely on spreading high amounts of individuals and are more vulnerable in their early stages than in their growing and adult phases. Thus, this approach can improve the capacity for mapping invasive species’ distributions at local scales, and the conservation efforts to control biolog- ical invasions in estuaries and coastal ecosystems.